2020
DOI: 10.1007/s11469-020-00340-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Fear of COVID-19, Mental Health, and Preventive Behaviours Across Pregnant Women and Husbands: An Actor-Partner Interdependence Modelling

Abstract: The present cross-sectional study examined the actor-partner interdependence effect of fear of COVID-19 among Iranian pregnant women and their husbands and its association with their mental health and preventive behaviours during the first wave of the COVID-19 pandemic in 2020. A total of 290 pregnant women and their husbands (N = 580) were randomly selected from a list of pregnant women in the Iranian Integrated Health System and were invited to respond to psychometric scales assessing fear of COVID-19, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
213
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(239 citation statements)
references
References 30 publications
22
213
2
2
Order By: Relevance
“…Furthermore, at the time of data collection there was a lack of validated instruments on specific protective health measures (hand hygiene) which forced us to rapidly design an instrument that has not yet been validated. After the data collection of the current study, important work has been done to develop and validate preventive behavior questionnaires [33,34]. Another limitation is that we did not control for the increase in familywise error rate across multiple statistical tests.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, at the time of data collection there was a lack of validated instruments on specific protective health measures (hand hygiene) which forced us to rapidly design an instrument that has not yet been validated. After the data collection of the current study, important work has been done to develop and validate preventive behavior questionnaires [33,34]. Another limitation is that we did not control for the increase in familywise error rate across multiple statistical tests.…”
Section: Limitationsmentioning
confidence: 99%
“…To cite just a few, domestic violence, anxiety, and perinatal depression are rising in times of social isolation and emotional constraints. 5,6 We understand that OBGYN are the leading professionals in women's integral health care, and residents must take part on it. Finally, and of the uttermost importance, we still do not know how SARS-CoV-2 behaves in specific conditions of our field, such as in pregnancy 7 or oncology.…”
Section: Dear Editormentioning
confidence: 99%
“…As a significant life-threatening public health event, the COVID-19 pandemic deteriorates the mental health status of perinatal women, especially those with deficient support systems (e.g., limited contact with family and friends) ( 12 ). A recent study found that more than 1/3 of the perinatal women experienced depression during the outbreak ( 13 ), and pregnant women reported a higher rate of depression after the declaration of the COVID-19 pandemic (29.6% vs. 26.0%) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of the pregnant and postpartum women also expressed fear of being infected with COVID-19, and it has been shown that the fear of COVID-19 was significantly related to depression, anxiety, suicidal ideation, and poor psychological quality of life (QOL) ( 12 ). Luckily, current studies suggest that there is no direct evidence for intrauterine infection caused by vertical transmission in women who develop COVID-19 pneumonia in their third trimester ( 16 ).…”
Section: Introductionmentioning
confidence: 99%